The Diagnosis and Profile of Learning Difficulties in Mathematics of Gifted Students in a Boarding School - PAMUNGKAS, Tubagus; BUDININGSIH, Asri; WIDJAJANTI, Djamilah Bondan (International Journal of Psychosocial Rehabilitation, 2020)
The learning difficulty diagnosis is a crucial thing because such effort can be used by teachers to help improving the learning outcome of students. The learning disability encountered by students with various abilities, including the gifted students. This study aimed to diagnose the learning difficulties in mathematics of gifted students who live in a dormitory for math subject. The data were collected through the test done at school through the validated instrument. A quantitative research with statistics test was used as the study method by using Kruskal Wallis and Man Whitney tests. The study findings showed that 1) the dominant condition of the learning difficulties of gifted students in dormitory was moderate category of learning difficulties; 2) male students experienced more difficulties in learning mathematics compared to the female students; 3) the most dominant data of mathematics learning difficulties on gifted students are at moderate level, either for comparing the pair of numbers (BPB), the competency in arithmetic operations (TOP), and the fluency in number identification (LIA) or working memory (MK) indicators. The results of this study can be used as the recommendation for future studies and the technical steps in improving test scores, especially for math subject at dormitory-based schools.